Public–Private Mix Models of Tuberculosis Care in Pakistan: A High-Burden Country Perspective - Ullah, Waseem; Wali, Ahmad; Haq, Mahboob Ul; Yaqoob, Aashifa; Fatima, Razia; Khan, Gul Majid (Frontiers in Public Health, 2021)
Introduction: Pakistan ranks fifth in the globally estimated burden of Tuberculosis (TB) case incidence. Annually, a gap of 241,688 TB patients exists between estimated TB incidence and actual TB case notification in Pakistan. These undetected/missed TB cases initiate TB care from providers in the private healthcare system who are less motivated to notify patients to the national database that leads to significant under-detection of actual TB cases in the Pakistani community. To engage these private providers in reaching out to missing TB cases, a national implementation trial of the Public-Private Mix (PPM) model was cohesively launched by NTP Pakistan in 2014. The study aims to assess the implementation, contribution, and relative treatment outcomes of cohesively implemented PPM model in comparison to the non-PPM model. Methods: A retrospective record review of all forms (new and relapse) TB patients notified from July 2015 to June 2016 was conducted both for PPM- and non-PPM models Results: PPM model was implemented in 92 districts in total through four different approaches and contributed 25% (81,016 TB cases) to the national TB case notification. PPM and non-PPM case notification showed a strong statistical difference in proportions among compared variables related to gender (p <0.001), age group (p <0.000), and province (p <0.000). Among PPM approaches, General Practitioner and Non-Governmental-Organization facilities achieve a treatment success of 94%-95%; Private Hospitals achieve 82% success while Parastatals are unable to follow more than half of their notified TB cases. Discussion: PPM model findings in Pakistan are considerably consistent with countries that have prioritized PPM for an increasing trend in TB case notification to their national TB control programs. Different PPM approaches need to be scaled up in terms of PPM implemented districts, PPM coverage, PPM coverage efficiency, and PPM coverage outcome in the Pakistani healthcare system in the future.